Circularly Polarized Quad-Port MIMO Dielectric Resonator Antenna with Beam Tilting Feature for Vehicular Communication. Issue 2 (4th March 2022) - Dwivedi, Ajay Kumar; Sharma, Anand; Singh, Ashutosh Kumar; Singh, Vivek
Abstract : In this article, a novel configuration of ring dielectric resonator-based multiple input multiple output antenna (MIMO) is proposed with a beam tilting characteristic. To achieve the beam tilting and low correlation among the far-field patterns, the conducting plate is positioned in between the antenna elements. Dual resonating frequencies are obtained by exciting the ring DRA electromagnetically with a microstrip line via optimized double-ring loaded slots. All the ports are arranged in a parallel fashion. Port-1/port-2 is placed 180 0 out of phase with port-3/port-4. The proposed antenna achieves the maximum beam tilting of 55 0 and 35 0 at 2.61 and 2.95 GHz, respectively. Polarization diversity is confirmed between oppositely oriented ports i.e. port-1/port-2 and port-4/port-3 by getting LHCP and RHCP patterns, respectively. The optimum value of diversity parameters of the proposed MIMO ring DRA makes it suitable for high-speed applications.